THE MARKETING PLAN IN THE WINE PRODUCING COMPANIES IN PORTUGAL (Revista Lusófona de Economia e Gestão das Organizações, 2018)
The creation of a marketing plan is something that has been studied and brings benefits to companies.The goal of this article transcribes the results of research, conducted on Portuguese wine companies, about the development and implementation of a marketing plan.We researched literature regarding context, benefits and barriers of the marketing plan and questioned the biggest 50 wine producing companies - responsible for 61, 6% of total wine production - in mainland Portugal (2009/2010).65% of respondents did not have a marketing plan: they simply set some goals and tried to react to what happens in the market. The main reasons presented for not having a marketing plan are the lack of available human resources and the lack of a suitable model/template to be applied to the company.The results indicated that the marketing plan is made annually and, the responsible for their implementation are mainly, marketing directors with the approval of top management. The advantages of the marketing plan outlined by the companies are: marketing plan helps to think about what the firm will do in the future, helps to organize the work and to assess and monitorizes the company’s performance. In this study are also listed the main elements that comprise marketing plan and the most important ones for companies - as well as the type of packaging used, the criteria for settingprices, distribution and the most used actions of communication.The method of collect data was done through the creation of a questionnaire online.The study universe is the Portuguese wine companies. The sampling method is not probabilistic. Sample´s method selection is intentional.